From complexity to integration: Insights for process design from an empirical case study of transdisciplinary planetary health collaboration in Indonesia - Jane Wardani; Joannette J. (Annette) Bos; Diego Ramirez-Lovering; Anthony G. Capon (Earth System Governance)
Transdisciplinary research has been increasingly advocated as necessary to address complex planetary health challenges spanning environmental and human health in different socio-economic contexts. Recognising global interdependence, such research must engage in equitable co-production for lasting, meaningful impact. Existing transdisciplinarity frameworks and practices from the environment, health, and development fields primarily focus on research processes and outcomes, generically mentioning ‘collaboration’ without sufficiently expanding how the process can be designed to facilitate equitable and sustained outcomes. This case study undertakes an empirical deep-dive into a planetary health research in Indonesia to better understand transdisciplinary collaboration from participants' experiences. Deductive and inductive analyses of the enabling and constraining factors offer novel insights into the collaborative process of stakeholder engagement, interaction, and integration. Rich examples from the case study were then synthesised into process design strategies to overcome structural constraints through boundary spanning, adaptive project management, and creating spaces for social learning and reflexivity. (150 words).